Ecophysiology and metabolites of biofilm-forming strains of the microalgal genus Jenufa (Chlorophyceae). Issue 4 (4th July 2022) - Zammit, Gabrielle; Agius, Maria
ABSTRACT: Microbial biofilms colonizing cultural heritage sites are detrimental due to the production of exudates which deteriorate archaeological surfaces. In this study, a number of microalgal strains isolated from biofilms in hypogea and catacombs were investigated using a multiphasic approach to describe their diversity. Microscopic observations and genetic analyses revealed that the minute coccoid cells belonged to the genus Jenufa . For the first time, ecophysiological characteristics of Jenufa spp strains have been studied and their intracellular, capsular and secreted metabolites quantified. Optimal growth was achieved in nutrient-rich conditions, in which the cells produced substantial amounts of cellular, capsular, colloidal and secreted metabolites. The capsule was composed of high amounts of protein. Under nutrient limitation, Jenufa spp cells produced high quantities of carbohydrates. Both Jenufa cells growing in situ on archaeological surfaces and those cultured in vitro were capable of sustained growth and active secretion of exopolymers for extended periods of time with minimal input of nutrients from outside sources.